The response of ionospheric convection in the polar cap to substorm activity - M. Lester; M. Lockwood; T. K. Yeoman; S. W. H. Cowley; H. Lühr; R. Bunting; C. J. Farrugia (Annales Geophysicae, 1995)
We report multi-instrument observations during an isolated substorm on 17 October 1989. The EISCAT radar operated in the SP-UK-POLI mode measuring ionospheric convection at latitudes 71°λ-78°λ. SAMNET and the EISCAT Magnetometer Cross provide information on the timing of substorm expansion phase onset and subsequent intensifications, as well as the location of the field aligned and ionospheric currents associated with the substorm current wedge. IMP-8 magnetic field data are also included. Evidence of a substorm growth phase is provided by the equatorward motion of a flow reversal boundary across the EISCAT radar field of view at 2130 MLT, following a southward turning of the interplanetary magnetic field (IMF). We infer that the polar cap expanded as a result of the addition of open magnetic flux to the tail lobes during this interval. The flow reversal boundary, which is a lower limit to the polar cap boundary, reached an invariant latitude equatorward of 71°λ by the time of the expansion phase onset. A westward electrojet, centred at 65.4°λ, occurred at the onset of the expansion phase. This electrojet subsequently moved poleward to a maximum of 68.1°λ at 2000 UT and also widened. During the expansion phase, there is evidence of bursts of plasma flow which are spatially localised at longitudes within the substorm current wedge and which occurred well poleward of the westward electrojet. We conclude that the substorm onset region in the ionosphere, defined by the westward electrojet, mapped to a part of the tail radially earthward of the boundary between open and closed magnetic flux, the "distant" neutral line. Thus the substorm was not initiated at the distant neutral line, although there is evidence that it remained active during the expansion phase. It is not obvious whether the electrojet mapped to a near-Earth neutral line, but at its most poleward, the expanded electrojet does not reach the estimated latitude of the polar cap boundary.